Experiences of College Students With Children During the COVID-19 Pandemic. Issue 5 (October 2021) - Manze, Meredith G.; Rauh, Lauren; Smith-Faust, Polly; Watnick, Dana
College students with children are a unique subset of emerging adults, whose lives were disrupted by the COVID-19 pandemic, challenging their pursuit for education and financial independence. We sought to understand barriers and facilitators to their academic persistence during the first wave of COVID-19 in New York City. We conducted 37 in-depth interviews with students, faculty, and staff at six community colleges within a public university about their experiences during the pandemic and analyzed data using a modified approach to grounded theory. Students, faculty, and staff recognized the magnified and expanded roles and responsibilities of student parents. Students discussed the challenges they endured because of the diminished time from these new responsibilities. They shared strategies implemented and sacrifices made to manage. Support from faculty and staff was critical to their academic persistence. Increased faculty flexibility and synthesizing information about remote resources can help student parents better manage during the pandemic.